PERWAKAFAN TANAH DAN PENDAFTARANNYA PASCA BERLAKUNYA UU. NO. 41 TAHUN 2004 TENTANG WAKAF DI KOTA SEMARANG - Afif Noor (Masalah-Masalah Hukum, 2011)
Land wakaf is an action that has institutionalized in the structure of Indonesian society. In order to improve surety and legal protection for the existence of wakaf, Act No. 41 Year 2004 concerning Wakaf is created as the center of the regulation of Wakaf in Indonesia. In connection with land wakaf, based on the research, it is found that the regulation of land wakaf after the legalization of wakaf Act is clearer and stricter also more detailed in regulating various matters related to wakaf compared to the previous regulation. In relation to the area of land wakaf, the total area of land wakaf that has been registered in the Land-Affairs Office of Semarang City is as much as 56, 457. 4 m2, scattered at 104 locations in Semarang City region. Meanwhile, the area of land that has not been registered at the Land-Affairs Office of Semarang City is as much as 6, 015 m2, scattered at 29 locations in 7 districts. There are several factors hindering the implementation of Wakaf Act demanding to perform the registration of land wakaf after the legalization of Wakaf Act, which are, lack of socialization from the related institutions about the importance of performing registration of land wakaf, legal awareness of the caretakers of land wakaf that is still relatively low, and unavailability of fund used for performing registration of land wakaf.